Graphene-based thermoplastic composites and their application for LED thermal management. (June 2016) - Cho, Er-Chieh; Huang, Jui-Hsiung; Li, Chiu-Ping; Chang-Jian, Cai-Wan; Lee, Kuen-Chan; Hsiao, Yu-Sheng; Huang, Jen-Hsien
Abstract: In this article, the polyamide (PA)/reduced graphene (rGO) nanocomposites used for thermally conductive materials have been synthesized through melting blending. A titanate coupling agent (TCA) is used to modify the rGO to enhance the chemical compatibility between rGO and PA. The results suggest that the covalent bonds can be formed by the chemical reaction between alkoxy group of titanate molecules and hydroxyl groups on the graphene oxide (GO). With the interfacial modification, the rGO can be dispersed well within the PA matrix. Moreover, the TCA molecule can replace of water of hydration at the rGO surface, which can eliminate the air voids within the composites resulting in better thermal conductivity. The LED lamp incorporated with the rGO based composite as heat sink also display better durability due to its excellent thermal dissipation.